Hydrological Changes in Restricted Basins: Insights From Strontium Isotopes on Late Miocene‐Pliocene Connectivity of the Eastern Paratethys (Dacian Basin, Romania). (12th July 2021) - Vasiliev, Iuliana; Stoica, Marius; Grothe, Arjen; Lazarev, Sergei; Palcu, Dan Valentin; van Baak, Christiaan; De Leeuw, Arjan; Sangiorgi, Francesca; Reichart, Gert‐Jan; Davies, Gareth R.; Krijgsman, Wout
Abstract: The Dacian Basin was uniquely situated to record late Miocene hydrological changes that influenced depositional environments and faunal dispersal patterns in Central Eurasia's mega‐lake Paratethys. Differences between the high strontium isotope ratio ( 87 Sr/ 86 Sr) of the waters from Lake Pannon and local Carpathian rivers and low 87 Sr/ 86 Sr of the Eastern Paratethys (Black Sea ‒ Caspian Sea) allow a thorough investigation of connectivity and water fluxes in the transient Dacian Basin. We present a detailed 87 Sr/ 86 Sr record for the Dacian Basin, which provides an exceptional record of basin connectivity from the latest Tortonian (ca. 7.7 Ma) until the early Pleistocene (ca. 1.8 Ma). Data show that a late Tortonian transgression (7.6–7.4 Ma) started with an incursion of Eastern Paratethys waters into the Dacian Basin, after which local rivers became the dominant source for the mostly freshwater environments of the early Messinian. The regional Maeotian‐Pontian transitional interval (6.3–5.9 Ma) records a second incursion of Eastern Paratethys waters, but this time with an additional marine (Mediterranean) influx coinciding with a short‐lived salinity incursion. During the Messinian Salinity Crisis of the Mediterranean, the Dacian Basin progressively connected with the Eastern Paratethys (5.9–5.5 Ma), after which it became restricted during the peak Mediterranean lowstand (5.5 Ma) and filled with Lake Pannon and local river water (5.5–5.3 Ma). During the Plio‐Pleistocene, the Dacian Basin reconnected with the, at that time isolated, Black Sea, which shows similar 87 Sr/ 86 Sr as in the Last Glacial Maximum. Plain Language Summary: The late Miocene Dacian Basin (western appendix of the Black Sea) was uniquely situated to record hydrological changes that influenced environments and faunal dispersal patterns in Central Eurasia's mega‐lake Paratethys. We used strontium isotopes from the Dacian Basin to track the moments of changing connections with Paratethys and the open ocean, via the Mediterranean. We found that at 7.6–7.4 Ma, an invasion of Eastern Paratethys waters provoked the so‐called Maeotian transgression. Afterward local rivers became the dominant source for the mostly freshwater environments, interrupted at 6.1 Ma by an influx of marine, salty water from Mediterranean. During the Messinian Salinity Crisis (5.9–5.3 Ma), when the Mediterranean suffered from an interrupted connectivity to the Atlantic Ocean, the Dacian Basin progressively connected with the Eastern Paratethys (Black Sea and Caspian Sea). At the peak of Messinian Salinity Crisis in the Mediterranean (5.5 Ma), the Dacian Basin became restricted and filled with Lake Pannon and local river water (5.5–5.3 Ma). During the Plio‐Pleistocene (between 5.3 and 1.8 Ma), the Dacian Basin reconnected with the, at that time isolated, Black Sea, providing a situation similar to the one during the Last Glacial Maximum. Key Points: The early Maeotian transgression (7.6–7.4 Ma) started with an incursion of Eastern Paratethys (i.e., Black Sea) waters into the Dacian Basin The Maeotian‐Pontian transition (6.3–5.9 Ma) records a second incursion of Eastern Paratethys followed by a short influx of marine (Mediterranean) waters The Bosphorian transgression at ca. 5.5 Ma was probably related to the increased influence of Pannonian and local river water in the Dacian Basin